Charge Density Wave Order and Fluctuations above T CDW and below Superconducting Tc in the Kagome Metal CsV3Sb5 - Chen, Q.; Chen, D.; Schnelle, W.; Felser, Claudia; Gaulin, B. D. (Physical Review Letters, 2022)
The phase diagram of the kagome metal family AV3Sb5 (A=K, Rb, Cs) features both superconductivity and charge density wave (CDW) instabilities, which have generated tremendous recent attention. Nonetheless, significant questions remain. In particular, the temperature evolution and demise of the CDW state has not been extensively studied, and little is known about the coexistence of the CDW with superconductivity at low temperatures. We report an x-ray scattering study of CsV3Sb5 over a broad range of temperatures from 300 to ∼2 K, below the onset of its superconductivity at Tc∼2.9 K. Order parameter measurements of the 2×2×2 CDW structure show an unusual and extended linear temperature dependence onsetting at T∗∼160 K, much higher than the susceptibility anomaly associated with CDW order at TCDW=94 K. This implies strong CDW fluctuations exist to ∼1.7×TCDW. The CDW order parameter is observed to be constant from T=16 to 2 K, implying that the CDW and superconducting order coexist below Tc, and, at ambient pressure, any possible competition between the two order parameters is manifested at temperatures well below Tc, if at all. Anomalies in the temperature dependence in the lattice parameters coincide with TCDW for c(T) and with T∗ for a(T).
CRIS-Team Scopus Importer:2023-03-20